Identification of target genes of PEA3, an ETS family transcription factor - Ellison, Jason (My University, 2001)
PEAS is a transcription factor of the ETS family, which has been implicated in mammalian development, tumorigenesis, and tumor progression. An attempt has been made to identify genes whose transcription is regulated by this factor in order to help elucidate its role in these processes. Cell lines, designated RP2, RP10 and RP11, were generated in which PEA3 overexpression can be induced at both the mRNA and protein levels. PEA3 overexpression in these cell lines is accompanied by activation of transcription of known PEA3 target genes such as MMP-9 and MMP-14 . Control cell lines, identical to these except for the lack of inducible PEA3 , show no such activation of PEA3 target genes under the same conditions. In order to identify PEA3 target genes mRNA isolated from RP 10 cells before and after induction of PEA3 overexpression was compared by Differential Display-Reverse Transcription PCR A number of mRNAs were identified that are coordinately upregulated with PEA3 . These include the mRNA that encodes Activated Leukocyte Cell Adhesion Molecule (ALCAM), which is a strong candidate PEA3 target. Activation of ALCAM transcription occurs in RP10 cells upon induction of PEA3 overexpression, but not in control cell lines. Similarly, activation of ALCAM transcription occurs in serum starved wild-type MEF cell lines upon induction of PEA3 expression by the addition of EGF, but not in PEA3 -null MEF cell lines under the same conditions. Finally, PEA3 is able to activate the expression of reporter genes downstream from fragments of the ALCAM promoter that contain consensus PEA3-binding sites.
Keywords: Biochemistry; Biochemistry